Islam in Europe : Public Spaces and Civic Networks - Sofos, Spyros A.; Tsagarousianou, Roza.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
Drawing upon extensive fieldwork and suggesting novel ways of approaching the phenomenon of European Islam and the continent's Muslim communities, Islam in Europe examines how European Muslims construct notions or identity, agency and belonging, how they negotiate and redefine the notions of religion, tradition, authority and cultural authenticity.
Keywords: Science; Science, general